Sustainable Water Quality Improvement in Small-Scale Tilapia Ponds Through Bio-DHS Filtration - Norfariza Ab Wahab; Nurul Fariha Lokman; Adlin Nur; Yamaguchi Takeshi; Tay Chia Chay; Suhaila Mohd Najib; Khusna Dwijayanti (International Journal of Integrated Engineering, 2025)
This study investigates the performance of Bio-Downflow Hanging Sponge (Bio-DHS) filtration in improving water quality for small-scale Tilapia aquaculture, addressing sustainability and resource efficiency challenges. The Bio-DHS system introduces a zero-exchange water management approach, eliminating the need for water replacement by only adding small amounts to compensate for evaporation and sampling losses. This method aligns with SDG 12 (Responsible Consumption and Production) by promoting efficient water use and minimizing waste discharge. Results revealed progressive improvements in water quality, including reductions in Biological Oxygen Demand (BOD), Total Suspended Solids (TSS), and Chemical Oxygen Demand (COD). Dissolved Oxygen (DO) levels increased to 7.00 mg/L during full-capacity operation, while nitrification efficiency reached 41.66%, indicating effective nitrogen cycling. The Water Quality Index (WQI) improved from 54.31 (polluted, Class III) without filtration to 68.20 (slightly polluted, Class III) with Bio-DHS filtration. While Class III water is suitable for aquaculture, fishery and livestock drinking, further optimization—such as extending Bio-DHS contact duration—could enhance quality for broader applications. By reducing pollutant loads in aquaculture, this system also supports SDG 14 (Life Below Water) by mitigating environmental impact and promoting cleaner water bodies. The Bio-DHS system is scalable and adaptable, making small-scale Tilapia fish ponds a viable, cost-effective solution for sustainable aquaculture in Malaysia. Future research should focus on optimizing microbial development and operational parameters to achieve higher WQI classifications.